2016
DOI: 10.1177/1077559516668274
|View full text |Cite
|
Sign up to set email alerts
|

Promoting First Relationships®

Abstract: We conducted a community-based randomized control trial with intent-to-treat analysis on Promoting First Relationships® (PFR), a 10-week home visiting program. The study included 247 families with 10–24-month-old children who had a recent, open Child Protective Services investigation of child maltreatment. Families were randomly assigned to receive either the 10-week, home visiting PFR service or a telephone-based, 3-call resource and referral (R&R) service. Across post-intervention time points, parents in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 32 publications
0
22
0
4
Order By: Relevance
“…Seven of the nine studies were randomized controlled trials (Chaffin et al, 2004(Chaffin et al, , 2011(Chaffin et al, , 2012Jonson-Reid et al, 2018;Jouriles et al, 2010;MacMillan et al, 2005;Oxford et al, 2016). One study, the first SafeCare trial, used a matched comparison group with no randomization to condition (Gershater-Molko et al, 2002), and Study 6 (NPP) was a state-wide pre-post trial with no comparison group (Maher et al, 2011).…”
Section: Methodological Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven of the nine studies were randomized controlled trials (Chaffin et al, 2004(Chaffin et al, , 2011(Chaffin et al, , 2012Jonson-Reid et al, 2018;Jouriles et al, 2010;MacMillan et al, 2005;Oxford et al, 2016). One study, the first SafeCare trial, used a matched comparison group with no randomization to condition (Gershater-Molko et al, 2002), and Study 6 (NPP) was a state-wide pre-post trial with no comparison group (Maher et al, 2011).…”
Section: Methodological Approachesmentioning
confidence: 99%
“…Participant numbers ranged from 35 in the Project Support RCT (Jouriles et al, 2010) to 2,175 in the state-wide SafeCare trial (Chaffin, Hecht, Bard, Silovsky, & Beasley, 2012), with a total of 3,615 participants across nine studies (see Online Appendix 1). In all studies, the participants had previous or current CPS involvement (Chaffin et al, 2004;Gershater-Molko, Lutzker, & Wesch, 2002;Jouriles et al, 2010;Maher, Marcynyszyn, Corwin, & Hodnett, 2011), were reported as being an "open case" with CPS (Oxford, Spieker, Lohr, & Fleming, 2016), and/or were referred for intervention by CPS (Chaffin et al, 2011(Chaffin et al, , 2012Jonson-Reid et al, 2018). Five of the nine studies reported mean number of prior CPS reports among the study's sample.…”
Section: Participants and Criteria For Inclusionmentioning
confidence: 99%
See 3 more Smart Citations